Cohesin organizes 3D DNA contacts surrounding active enhancers in C. elegans - Kim, Jun; Wang, Haoyu; Ercan, Sevinç (Genome Research, 2025)
In mammals, cohesin and CTCF organize the 3D genome into topologically associating domains (TADs) to regulate communication between cis-regulatory elements. Many organisms, including S. cerevisiae, C. elegans, and A. thaliana contain cohesin but lack CTCF. Here, we used C. elegans to investigate the function of cohesin in 3D genome organization in the absence of CTCF. Using Hi-C data, we observe cohesin-dependent features called “fountains,” which have also been reported in zebrafish and mice. These are population average reflections of DNA loops originating from distinct genomic regions and are ∼20–40 kb in C. elegans. Hi-C analysis upon cohesin and WAPL-1 depletion supports the idea that cohesin is preferentially loaded at sites bound by the C. elegans ortholog of NIPBL and loop extrudes in an effectively two-sided manner. ChIP-seq analyses show that cohesin translocation along the fountain trajectory depends on a fully intact complex and is extended upon WAPL-1 depletion. Hi-C contact patterns at individual fountains suggest that cohesin processivity is unequal on each side, possibly owing to collision with cohesin loaded from surrounding sites. The putative cohesin loading sites are closest to active enhancers, and fountain strength is associated with transcription. Compared with mammals, the average processivity of C. elegans cohesin is about 10-fold shorter, and the binding of NIPBL ortholog does not depend on cohesin. We propose that preferential loading and loop extrusion by cohesin is an evolutionarily conserved mechanism that regulates the 3D interactions of enhancers in animal genomes.